2021
DOI: 10.3390/su13126639
|View full text |Cite
|
Sign up to set email alerts
|

Partnering for Sustainability: Parent-Teacher-School (PTS) Interactions in the Qatar Education System

Abstract: The interaction avenues, levels, and impacts between parents, schools and teachers have changed drastically due to the ever-increasing responsibilities, frequent and rapid changes in the curriculum, the invasive dominance of the internet and digital media in the lives of all stakeholders, and the digitization of learning materials, to name a few. This pilot study follows a design-thinking approach to investigate the current practices, needs, and challenges of parental involvement in public schools in Qatar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…The relationship between perceived levels of communication, psychosocial aspects, and perceived stress were found to be positively correlated in this study. Communication has previously been established as a protective factor from distress among school children, and improved well-being across the various stakeholders [ 26 , 29 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between perceived levels of communication, psychosocial aspects, and perceived stress were found to be positively correlated in this study. Communication has previously been established as a protective factor from distress among school children, and improved well-being across the various stakeholders [ 26 , 29 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of COVID-19, school closures have shifted education from the classroom to the home, where parents had to fill an educational role as well (at least partially) [ 25 ]. It has previously been widely discussed in the scientific literature that communication between various stakeholders of school systems promotes improved well-being for all [ 26 , 27 , 28 , 29 ]. The findings of Lv et al, {2016} indicate that parent–teacher/ school communication plays an important moderating role in student emotional well-being and academic achievement, and Kuusimaki and Uusitalo-Malmivaara (2019) found that interactions between parents and teachers improve the well-being of teachers [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conflicts between teachers and students result from disciplinary actions, with students resisting punishments that disrupt their academic pursuits [27]. Parents cite disagreements over academic performance and corporal punishment as triggers for conflicts with teachers, while teachers point to parents making decisions without verifying facts [29]. An internal conflict emerges between teachers and employers due to low wages, teachers taking part-time jobs, and violating employer requirements [25].…”
Section: Fig 1 Frequency Of Conflict Incidents In Secondary Schoolsmentioning
confidence: 99%
“…Penggunaan bentuk kegiatan kerja dan keterlibatan orang tua dalam kerja sama aktif akan memungkinkan pemecahan masalah. Seperti pada penelitian sebelumnya (Al-Hail et al, 2021), salah satu solusi ini adalah pengembangan kegiatan proyek konten lingkungan oleh guru dengan keterlibatan orang tua dalam kerja sama aktif. Ini akan memungkinkan untuk menggabungkan kegiatan belajar, bermain dan bekerja secara harmonis, di mana setiap tindakan anak menjadi alat pengetahuannya, penemuannya sendiri, cara untuk memahami kebenaran (Gianoutsos, 2006).…”
Section: Gambar 3 Pengaruh Kemampuan Literasi Lingkungan Bermuatan Tr...unclassified